2022
DOI: 10.3390/life12122026
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psoriasis and Atopic Dermatitis on Quality of Life: A Literature Research on Biomarkers

Abstract: Psoriasis (PSO) and Atopic dermatitis (AD) are common inflammatory skin diseases that affect people of all ages globally. They negatively impact the quality of life (QoL) of patients in health-related aspects such as physical, psychological and mental functioning. Here, we conducted a review of studies relating to candidate biomarkers and indicators associated with QoL impairment in PSO and AD. Data research was performed using PUBMED and SCOPUS databases from inception to September 2022. Most of the included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 134 publications
(204 reference statements)
0
7
1
Order By: Relevance
“…Our analysis did not establish a significant association between DLQI scores and age, sex, or comorbidities, in contrast to some previous studies 35–37 . This difference may be attributed to variations in study populations and treatment modalities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our analysis did not establish a significant association between DLQI scores and age, sex, or comorbidities, in contrast to some previous studies 35–37 . This difference may be attributed to variations in study populations and treatment modalities.…”
Section: Discussioncontrasting
confidence: 99%
“…34 Our analysis did not establish a significant association between DLQI scores and age, sex, or comorbidities, in contrast to some previous studies. [35][36][37] This difference may be attributed to variations in study populations and treatment modalities. Previous studies on patient-reported outcomes in psoriasis often included topical Our study has some limitations that should be acknowledged.…”
Section: Ta B L Ementioning
confidence: 99%
“…A lot of effort has been made to identify biomarkers that would best reflect the disease onset and progression [10]. However, a reliable marker that would differentiate PsO from AD has rarely been examined [11,12] and has not been established yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although the hyperproliferation of keratinocytes is the most remarkable characteristic of PS, the underlying mechanism of the loss of control is not well studied. Environmental factors, genetic background, and immune responses may be involved in the pathogenesis of PS [ 10 ]. Although the immunopathological mechanisms underlying this disease with defective immune responses are not yet fully understood, research has highlighted the significant roles played by immune cells located in the dermis and epidermis, such as dendritic cells (DCs) and T lymphocytes (T cells) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%